2004
DOI: 10.1103/physrevb.69.220413
|View full text |Cite
|
Sign up to set email alerts
|

Large inverse magnetoresistance ofCrO2Cojunctions with an artificial barrier

Abstract: We report on magnetotransport measurements on magnetic junctions consisting of Co and half-metallic CrO 2 as the electrodes. The insulating barrier in between is a CrO x -AlO x layer created via a chemical modification of the native CrO 2 surface, followed by the deposition and oxidation of a thin Al layer. The junctions exhibit a hysteretic low-field magnetoresistance with switching closely matching that of the magnetization of the CrO 2 and Co layers. The magnetoresistance is inverse in sign, with a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…9,10 The films are patterned into 50ϫ 200 m 2 Hall bar structures using optical lithography and wet chemical etching. For the magnetotransport experiments, the samples are mounted in a superconducting magnet system and the sample temperature is stabilized using a variable temperature insert.…”
mentioning
confidence: 99%
“…9,10 The films are patterned into 50ϫ 200 m 2 Hall bar structures using optical lithography and wet chemical etching. For the magnetotransport experiments, the samples are mounted in a superconducting magnet system and the sample temperature is stabilized using a variable temperature insert.…”
mentioning
confidence: 99%
“…(4) and (5). Meanwhile, in Mg rich limit ( μ Mg = 0 eV), the value of Γ equals −0.0469 eV/Å [2], which means this structure, corresponding B-Mg interface, is stable under Mg rich condition. It also can be observed from Fig.…”
mentioning
confidence: 92%
“…A wide variety of functional thin films grown epitaxially on different substrates have received much attention because of their importance in many technological applications [1][2][3][4][5][6][7][8]. For instances, oxide films epitaxially on metal substrates can be applied for microelectronics, catalysis, magnetic tunnel junctions, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] These properties make chromium dioxide a promising material to be used in magnetoresistive structures such as spin valves and magnetic tunnel junctions. [6][7][8] Moreover, Keizer et al [9] showed that CrO 2 could be used in magnetization-controlled Josephson junctions in which supercurrents can be switched with the direction of the magnetization, similar to spin valve transistors. Although much effort has been put into developing efficient and controlled methods for preparing CrO 2 thin films, their synthesis at moderate pressures and temperatures is a nontrivial and challenging task due to the metastability of this oxide.…”
Section: Introductionmentioning
confidence: 98%